Everyday Self-Care : the little book that helps you to take care of YOU - Bates, Dawn (London : CICO Books, 2020)
Discover why time spent caring for yourself is always time well spent, and the countless ways you can improve your health, happiness and wellbeing.
Keywords: Self-actualization (Psychology); Psychology